POLALANTA DIVORCE PRACTICE OF BANGGAI ETHNIC SOCIETY IN BANGGAI DISTRIC BASED ON ISLAMIC LAW AND CONSTITUTIONAL LAW - Adiyanto Mutalib; Nasaruddin Nasaruddin; Hilal Malarangan (Risalah, Jurnal Pendidikan dan Studi Islam, 2022)
This paper aims to describe The issue of divorce between Islamic law and constitutional law which is very distinction, one of argumentation in Islamic law; according to one opinion, divorce only needs to be witnessed, while in constitutional law, divorce must be tried in the Religion Courts. This provision is contained in Article 39 paragraph (1) of Law No.1 of 1974, Article 65 of Law No.3 of 2006, and Article 115 of the Compilation of Islamic Law, which stipulates that divorce can only be carried out in front of a Court session after the court concerned tried and failed to reconcile the two parties.